Clinical characteristics in immune thrombocytopenia patients after COVID-19 vaccination - Yimei Feng; Yao Quan; Kaniel Cassady; Zhongmin Zou; Yuan Gao; Xi Zhang (Taylor & Francis Group, 2022)
It is well documented that COVID-19 vaccines greatly reduce the severity and complications of SARS-CoV-2 infection. However, it has been reported that COVID-19 related vaccines may induce or exacerbate autoimmune hematological disorders, for example, a decrease in platelet numbers characteristic of immune thrombocytopenia (ITP). To investigate this, we retrospectively reported, for the first time, the clinical characteristics of 42 ITP patients after COVID-19 vaccination in southwest China. Of the 42 patients, 28 patients were historically diagnosed ITP, and their platelet counts (PC) decrease mainly occurred after the first-dose vaccinations. The average PC after vaccination was 39.5 × 109/L and recovered to an average of 80.6 × 109/L after treatment. Efficacy of treatment was 90%, and only 10% maintained low PC at the third month of treatment. More interestingly, of the 42 patients, 14 were newly diagnosed ITP following vaccination. Of these 14 patients, 6 patients (43%) were found PC deterioration after the first vaccine dose, and 7 patients (50%) after the second dose. Fortunately, the peripheral PC of all 14 patients recovered significantly after treatment, and the average PC was 139.4 × 109/L, including 8 CRs (complete response) and 6 PRs (partial response). Notably, 9 of the 14 cases were found to have abnormal immune indices when thrombocytopenia diagnosed. No severe organ hemorrhage was found in either subgroup. These results are reassuring the vaccine safety for ITP patients, in that the risks of aggravating thrombocytopenia by COVID-19 vaccination do exist, but it was transient and can be effectively controlled through intensive clinical monitoring and management.